The Role of Saudi Universities in Activating Investment Committees In the light of the New Saudi Universities Financial Regulations - Dakhil Al-Tayyar, Muhanad bin Saud; bin Hamad Al-Hawas, Hamad bin Khalid (Journal of Tikrit University for Humanities, 2024)
The study aimed to identify the role of Saudi universities in activating investment committees in light of the new financial regulations for Saudi universities, by reviewing the new university system according to the requirements of Vision 2030, and presenting proposals to activate university investment. The study used the descriptive analytical approach using the open-ended standardized interview to review and analyze the opinions of a number of (10) experts and specialists in this regulation, clarify the most prominent amendments that were made to it, and also identify the requirements and role of universities to activate investment committees in the best possible way in light of those regulations. The results of the study showed that Saudi universities have a major role in activating investment through the following: Establishing the legislation and legal systems to carry out the investment process. Training their staff. Providing the necessary infrastructure and superstructure. Exploiting its facilities to achieve the goals of investment. The roles of investment committees in universities also vary, including: Providing investment plans for education. Updating the database of investment assets. Collaborating with the private sector and working to improve the university’s efficiency in diversified investments. The study recommended the need to train Saudi university staff, benefit from global experiences, and simplify administrative procedures and regulations in the field of university funding.